The Direct and Indirect Effect of Spirituality and Self-Care on Quality of Life Among Patients with Chronic Kidney Failure - Budhiana, Johan; Elengoe, Asita; Said, Mohamed Saefulaman Mohamed (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: Chronic kidney failure (CKF) is a significant global health issue, with profound impacts on patients' quality of life (QoL). Self-care and spirituality have been identified as key determinants influencing QoL among CKF patients undergoing hemodialysis. However, the interactive effects of these factors remain underexplored, particularly in Indonesia. Objective: This study aims to investigate the direct and indirect effects of spirituality and self-care on QoL among CKF patients undergoing hemodialysis at Sekarwangi Hospital, Sukabumi Regency. Methods: A correlational research design was employed, involving 71 CKF patients undergoing routine hemodialysis. Participants were selected using purposive sampling based on inclusion criteria. Data were collected using validated instruments: the Hemodialysis Patients’ Self-Care Measurement Scale (HPSCMS), Spiritual Well-Being Scale (SWBS), and Kidney Disease Quality of Life Short Form (KDQOL-SF™ v1.3). Path analysis was conducted to assess the direct and indirect effects of spirituality and self-care on QoL. Results: Spirituality exhibited a significant direct effect on QoL (β = 0.381, p < 0.001) and an indirect effect through self-care (β = 0.384), with a total effect of 0.765. Self-care also had a significant direct effect on QoL (β = 0.547, p < 0.001). Higher spirituality and better self-care practices were associated with improved QoL in CKF patients. Conclusion: The findings underscore the importance of spirituality and self-care in enhancing QoL among CKF patients undergoing hemodialysis. Integrating spiritual support and promoting self-care behaviors into patient care could significantly improve outcomes. Future interventions should adopt a holistic approach, addressing both physical and spiritual dimensions of care.